2022
DOI: 10.1002/cbdv.202200436
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Effect of the Essential oils from Erigeron Canadensis L. on Human Cervical Cancer HeLa Cells in Vitro

Abstract: Erigeron Canadensis L. (E. canadensis) is a widely distributed invasive weed species in China. Potentially anticancer qualities may exist in its essential oils (EOs). The purpose of this study was to analyze the components of the EOs of E. canadensis and their effects on the normal liver cell lines L02 and the human cervical cancer cell lines HeLa. The EOs from the upper region of E. canadensis were prepared, its components were identified by GC/MS. Cell viability, cell morphology observation, AO/EB dual fluor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Carpesium abrotanoides' EO induces apoptosis via the intrinsic pathway in human hepatocellular carcinoma cells (HepG2) [65]. Finally, the Conyza canadensis EO induced apoptosis in the human cervical cancer HeLa cell line [66]. Based on our results, CBEO induces an antimelanoma effect by apoptosis induction.…”
Section: Discussionsupporting
confidence: 52%
“…Carpesium abrotanoides' EO induces apoptosis via the intrinsic pathway in human hepatocellular carcinoma cells (HepG2) [65]. Finally, the Conyza canadensis EO induced apoptosis in the human cervical cancer HeLa cell line [66]. Based on our results, CBEO induces an antimelanoma effect by apoptosis induction.…”
Section: Discussionsupporting
confidence: 52%
“…Surprisingly, C. pyriformis, which contained the highest proportion of limonene (70.4%), displayed the lowest antiproliferative activity. A few studies have highlighted that limonene might not be a primary contributor to the cytotoxicity of essential oils [ 49 , 50 , 51 ]. On the other hand, several other terpenes that are found in Citrus spp.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Moirangthem et al [87] reported that Cephalotaxus griffithii EO treatment induced cytoplasmic membrane blebbing, nuclear contraction, nuclear fragmentation, and the formation of apoptotic bodies in HeLa cells, associated with up-regulated expression of caspase-3, a central protein involved in the process of apoptosis. Similarly, Erigeron canadensis EO treatment led to increased expression of caspase-3, -9, and -12 proteins, nuclear pyknosis, and abnormal chromatin condensation in HeLa cells [88]. Additionally, EOs have been shown to induce cell cycle arrest by blocking cells in the G0/G1 phase [89][90][91].…”
Section: Role Of Essential Oils In Cervical Cancer: Evidence From Lab...mentioning
confidence: 99%